REUTILIZATION OF CONSTRUCTION AND DEMOLITION WASTE IN PERMEABLE PAVEMENTS: A SUSTAINABLE SOLUTION FOR URBAN INFRASTRUCTURE (International Seven Journal of Multidisciplinary, 2024)
The growing demand for environmentally sustainable solutions in civil construction has encouraged the reuse of construction and demolition waste (CDW) in innovative applications, such as the production of permeable pavements. These pavements allow rainwater to infiltrate into the ground, helping to mitigate flooding, relieve urban drainage systems, and promote aquifer recharge. Recent studies, including those by Rahman et al. (2015), Ossa et al. (2016), and Li et al. (2022), assessed the performance of materials such as recycled concrete, crushed bricks, and reclaimed asphalt in different compositions and combinations with geotextiles, demonstrating good hydraulic efficiency and pollutant filtration capacity. However, the presence of geotextiles may lead to progressive clogging, requiring continuous system maintenance assessment. Other studies, such as Strieder et al. (2022), evaluated permeable concretes with recycled aggregates, noting improvements in hydraulic properties, although with a reduction in mechanical performance. Field tests confirmed the feasibility of application, particularly with rigorous material quality control. In parallel, De Souza et al. (2021) emphasized the strategic value of patents in technological advancement, identifying 65 international patent records related to the use of CDW in permeable pavements, with the United States, Brazil, Japan, and China as leading applicants. Finally, Mohammadinia et al. (2017) demonstrated the effectiveness of lime stabilization to enhance the performance of CDW used in pavement base layers, especially for RCA and CB. The results point to a sustainable and technically viable alternative, contributing to the development of more resilient cities aligned with the principles of circular economy and sustainable urban development.